Pendampingan Anak Migran Indonesia dalam Membaca Al-Qur’an Melalui Metode Faṣoḥatī di PKBM PNF KBRI Kuala Lumpur - Irfani, Muhammad Zidan; A’yun, Qurroti; Suwari, Suwari (Civiliza Publishing, 2025)
The increasing number of Indonesian migrant children in Malaysia has created new challenges in religious education, especially in Qur'an reading skills which are influenced by the linguistic interference of the Malay language. In the PKBM PNF KBRI in Kuala Lumpur, vocal errors such as kasrah shifting to e and dhammah changing to o, as well as inaccuracies in makhraj became recurring problems. This service aims to improve the vocal accuracy and makhraj of migrant children through the consistent application of the Faṣoḥatī method in an unstable learning environment due to volunteer rotation. Using a service learning approach, the service was carried out for three weeks through participatory observation, in-depth interviews, field notes, and daily reflection which were analyzed through reduction, theme categorization, and source triangulation. The results showed a gradual improvement in vocal stability, makhraj accuracy, and reading rhythm. Children begin to distinguish the i and u sounds more precisely, improve the articulation of the letters of the throat, and show the courage to read in front of the class. Social impact is also seen through increased classroom collaboration and student self-awareness in correcting mistakes. The uniqueness of this program lies in the application of Faṣoḥatī in the context of the migrant community, which successfully functions as a technical method as well as a reflective social space that fosters phonetic courage and independence. This service recommends extending the duration, consistency of methods between volunteers, the preparation of standard modules, and family involvement to maintain the sustainability of results.